The effect of the extract of pasak bumi roots (Eurycoma longifoliaJack.) on liver function - Panjaitan, Ruqiah Ganda Putri; Manalu, Wasmen; Handharyani, Ekowati; ., Chairul (Indonesian Journal of Pharmacy, 2011)
The  aim  of  this  research  is  to  study  the  effects  of the  methanol  extract and  its  derived  fraction  (n-hexane,  chloroform,  ethyl  acetate,  and  methanolwater)  on  liver  function  of  male  rats.  The  treatment  groups  were  administered 500  mg/kg body weight of metanol extract and its derived fractions (n-hexane, chloroform,  ethyl  acetate,  n-butanol,  methanol-water)  of  E.  longifolia for  7 consecutive  days.  Positive  control  group  received  25  mg  silymarin/kg  body weight and negative control group received 2 mL aquadest/kg body weight daily for  7  consecutive  days.  Liver  function  was  monitored  by  measuring  alanine transaminase  (ALT),  aspartate  transaminase  (AST),  total  protein,  alkaline phosphatase  (ALP),  total  bilirubin,  direct  bilirubin,  and  indirect  bilirubin consentrations  in  the  serum.  Compared  with  control,  oral  administration  of methanol  extract  and  derived  fractions  of  methanol extract  of  E.  longifolia root had  no  significant  effects  on  liver  function  (p>0.05).  Methanol-water fraction gave similar results to silymarin.Key words: Eurycoma longfolia Jack.,liver function, biochemical blood Histopathologi